Good outcomes are more likely for me than you—Especially in a just world. (1st September 2020) - Strelan, Peter; Callisto, Jordana
Abstract: We conducted two studies with the aim of testing the new idea that believing in a just world for the self (BJW-self) encourages unrealistic bias about attaining positive outcomes and avoiding negative ones, relative to similar others, and that this relation would be accentuated when individuals perceived they had control over outcomes. Both studies were conducted online and employed correlational, survey-type designs. Study 1 ( N = 140) consisted of Australian university undergraduates (80 women, 58 men; two indicated 'other'; M age = 20, SD = 4.05). Study 2 ( N = 208) consisted of mostly North American and European and UK participants recruited through the website Prolific (131 males, 71 females, two transgender; M age = 24.35, SD = 3.16). BJW-self was positively associated with positive (Study 1) and valued (Study 2) outcomes, and negatively associated with negative (Study 1) and feared (Study 2) outcomes. There was a significant BJW-self × control interaction effect on probability of positive and valued outcomes, with the effect of BJW-self magnified when control was high (but not low). These findings demonstrate that BJW-self predicts not only positive future-oriented attitudes, behaviors, and characteristics, it also encourages a belief that, in the future, one will do even better than others. Highlights: The first studies to test relations between belief in a just world (BJW) and unrealistic bias BJW-self encourages unrealistic bias about experiencing positive outcomes and avoiding negative ones. Controllability perceptions are positively associated with experiencing positive outcomes and avoiding negative ones. Relations between BJW-self and unrealistic bias are magnified when individuals perceive high control over outcomes.